Effects of metformin on the heart with ischaemia-reperfusion injury: Evidence of its benefits from in vitro, in vivo and clinical reports - Louis Higgins (2019)
© 2019 Elsevier B.V. Ischaemia reperfusion (I/R) injury following myocardial infarction reperfusion therapy is a phenomenon that results in further loss of cardiomyocytes and cardiac contractility. Among the potential therapeutics to counter cardiac I/R injury, the antidiabetic drug metformin has shown promising experimental results. This review encompasses evidence available from studies of metformin's protective effects on the heart following cardiac I/R in vitro, ex vivo and in vivo, alongside clinical trials. Experimental data describes potential mechanisms of metformin, including activation of AMPK, an energy sensing kinase with many downstream effects. Suggested effects include upregulation of superoxide dismutases (SODs), which reduce oxidative stress and improve mitochondrial function. Additionally, metformin demonstrates anti-apoptotic effects, most likely by inhibiting mitochondrial permeability transition pore (mPTP) opening, and anti-inflammatory effects, by JNK inhibition. Recent reports of metformin's role in modulating complex I activity of the electron transport chain following cardiac I/R are also presented and discussed. Furthermore, clinical reports present mixed findings, suggesting that beneficial effects may depend on dosage, timing and condition of patients receiving metformin treatment. Conclusively there is an increased need for prospective, placebo-controlled clinical studies to confirm the mechanisms and to demonstrate that metformin is a suitable and safe drug for treatment of cardiac I/R injury.